Anti-Acne Gel of Quercetin Loaded Niosomes - Labade, Pratiksha; Pandit, Ashlesha; Chaudhari, Prafulla (Iranian Journal of Pharmaceutical Sciences, 2025)
We aimed to create a gel to treat acne. It contains quercetin-loaded niosomes. The thin film hydration method formulated quercetin-loaded niosomes made of cholesterol, maltodextrin, and span 60. The best batch of niosomes showed entrapment efficiency (97.10±0.10%), particle size (62.37±2µm), zeta potential (-43.4±6mv), and polydispersity index of 0.0554. The best batch (F7) was composed of quercetin (50 mg), Span 60 (180 mg), cholesterol (20 mg), maltodextrin (120 mg), hydration time (120 s), and hydration volume (30 ml). Further, F7 was subjected to a sonicator to reduce the particle size to 593.5±2.0 nm. Niosomes with spherical shapes were evenly dispersed, as shown by SEM analysis. Next, using a cold mechanical technique, quercetin niosomes loaded gel was prepared using carbopol 940. Gel exhibited a pH of 6.4, a high viscosity of 12,500 cP, quercetin diffusion through goat skin (93.56±2.19% within six h), and a zone of inhibition against Cutibacterium acnes (5.2± 0.9 mm). In conclusion, niosomal gel loaded with quercetin was thus shown to be a viable delivery strategy to treat acne.